Dynamic interaction between Isp45 and mitochondrial hsp70 in the protein import system of the yeast mitochondrial inner membrane. - Kronidou, N G (1994)
The protein import system of the yeast mitochondrial inner membrane includes at least three membrane proteins that presumably form a transmembrane channel as well as several chaperone proteins that mediate the import and refolding of precursor proteins. We show that one of the membrane proteins, Isp45, spans the mitochondrial inner membrane yet is extracted from this membrane at high pH. Solubilization of mitochondria with a nonionic detergent releases Isp45 as a complex with the chaperones mitochondrial hsp70 (mhsp70) and GrpEp. Both chaperones reversibly dissociate from Isp45 upon addition of ATP or adenosine 5'-[gamma-thio]triphosphate, suggesting that dissociation requires the binding of ATP. Control experiments indicate that the interaction between mhsp70 and Isp45 occurs in the intact mitochondria. We propose that Isp45 lines the inside of a proteinaceous channel across the inner membrane and that it is the membrane anchor for an ATP-driven "import motor" composed of mhsp70 and GrpEp. This arrangement is reminiscent of the protein transport systems of the yeast endoplasmic reticulum and the bacterial plasma membrane.